Communication Model of the Islamic Shari'ah Service in Implementing Islamic Shari'a Policies in Langsa City - Syukur Kholil; Yusnadi Yusnadi; Zulkarnain Zulkarnain (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines in depth the communication model of the Islamic Shari'a Service in implementing Islamic Shari'a policies in Langsa City, the themes that are communicated and the communication barriers faced. This research was designed with a qualitative descriptive approach. Data were collected by in-depth interviewing 11 informants who were taken purposively. Repeated observations of the location are also part of the data collection which is then analyzed using Miles and Huberman's interactive analysis techniques. The results of this study indicate that; First, there are two communication models commonly used by the Langsa City Islamic Shari'a Service in implementing Islamic Shari'a policies, namely the SMCRE (Source, Message, Channel, Receiver, Effect) communication model, and the chain and bitang communication model. Both of these communication models are practically applied in the form of interpersonal communication, group communication and mass communication. In the end, this study argues that a communication model that is relevant to the socio-demographic situation and condition of the community can support the effectiveness of the messages conveyed so that the community can support the implementation of Islamic law in Langsa City.